From starvation to depression: unveiling the link between the great famine and late-life depression - Lin Guo; Bin Sang; Shanna Li; Zhongming Xia; Meilin Li; Mengru Yang; Wenqiang Yin; Ying Liu (BMC Public Health)
Abstract Background The Great Famine in China from 1959 to 1961 is recognized as one of the most severe social and public health disasters of the 20th century, with profound long-term impacts on the health of survivors, particularly on their mental health. Early-life malnutrition and psychological trauma are considered to contribute to a range of health issues in adulthood, including depression. Objective This study aims to explore how the experience of the Chinese Great Famine from 1959 to 1961 affects the risk of depressive symptoms among the elderly. Using a mechanism analysis, the study investigates the roles of social support, socioeconomic status, and intergenerational support in this process. Methods Using micro-level individual data from the China Health and Retirement Longitudinal Survey (CHARLS), combined with province-level excess mortality data, this study employs a cohort-based difference-in-differences model to identify the causal effects of the famine experience on depression levels among the elderly. Results The study reveals that experiencing the Great Famine significantly increases the risk of depression among the elderly. This effect is more pronounced among rural residents, those who experienced the famine during adolescence, and in regions less influenced by Confucian culture. The mechanism analysis indicates that diminished social support, lower socioeconomic status, and insufficient intergenerational support are the primary pathways through which the famine experience influences depression levels in the elderly. Conclusions The experience of the Great Famine has exerted a long-term and profound impact on the mental health of the elderly in China, particularly in terms of depression. The findings provide new perspectives on understanding the long-term effects of major historical events on health and offer important empirical evidence for the development of mental health intervention policies for the elderly.